2011
DOI: 10.1002/lary.22344
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of upper airway obstruction by sleep videofluoroscopy in obstructive sleep apnea

Abstract: Even if multiplicity of obstruction pattern was most commonly associated with severe OSA, almost one third of mild OSA patients also showed multiple anatomic structures and levels of obstruction. Therefore, a precise evaluation for multiplicity of obstruction patterns should precede the decision of a treatment plan, regardless of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…Plain radiograph cephalometry meets ideals of simplicity, safety, and affordability, but with no dynamic imaging, sub-optimal resolution of critical soft tissue structures, and limitation to lateral views of the upper airway. Sleep videofluoroscopy provides dynamic visualization of the soft tissue of the airway and has been shown to localize single and multi-level obstruction during drug-induced sleep [19,20], but similarly to DISE this approach carries the burdens of a procedure under anaesthesia. While this retrospective study cannot yet provide definitive statements on the ultimate utility of MBS in characterizing obstruction, facilitating treatment planning, or improving surgical outcomes, it does provide preliminary support for the validity of anatomic measurement acquired by MBS, suggesting it could provide an accurate, low cost, and low risk means to assess the upper airway and merits further investigation into its utility as a new modality in evaluating OSA patients at low cost and low risk to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiograph cephalometry meets ideals of simplicity, safety, and affordability, but with no dynamic imaging, sub-optimal resolution of critical soft tissue structures, and limitation to lateral views of the upper airway. Sleep videofluoroscopy provides dynamic visualization of the soft tissue of the airway and has been shown to localize single and multi-level obstruction during drug-induced sleep [19,20], but similarly to DISE this approach carries the burdens of a procedure under anaesthesia. While this retrospective study cannot yet provide definitive statements on the ultimate utility of MBS in characterizing obstruction, facilitating treatment planning, or improving surgical outcomes, it does provide preliminary support for the validity of anatomic measurement acquired by MBS, suggesting it could provide an accurate, low cost, and low risk means to assess the upper airway and merits further investigation into its utility as a new modality in evaluating OSA patients at low cost and low risk to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies indicated that retropalatal region alone was the most common obstructed structure in mild OSAS, and the combination of the soft palate and the tongue base was more frequent in severe OSAS . However, other authors reported that retropalatal collapse was associated with OSAS due to an increased collapsibility of the lateral pharyngeal walls in this region .…”
Section: Discussionmentioning
confidence: 99%
“…The consensus between the MM findings and the apnea‐hypopnea index (AHI) has provided support to use MM in the detection and treatment of OSAS patients . However, there are disadvantages of the MM procedure, such as the inability to simultaneously show different levels of the obstruction, failure to reflect the sleeping breathing pattern because the maneuver is performed while the patient is awake and in the sitting position, inability to prevent voluntary motor activities while assessing dynamic pathologies, and incapability of every patient to create a sufficient negative pressure . For these reasons, drug‐induced endoscopy (DISE), which simulates sleep, minimizes the muscle activities in the upper airway, and inhibits voluntary movements, is thought to be the more accurate method to observe upper airway dynamics …”
Section: Introductionmentioning
confidence: 99%
“…7 Each of these obstruction structures alone can play a role in the pathogenesis of OSA. In this model, upper airway obstruction was induced by paralyzing only the main protrusor muscle of the tongue, the genioglossus.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Even if both the soft palate and tongue base levels are involved in the pathophysiology, it is difficult to assess which of the 2 anatomical sites is the primary etiology through human studies. [7][8][9][10] Even if both the soft palate and tongue base levels are involved in the pathophysiology, it is difficult to assess which of the 2 anatomical sites is the primary etiology through human studies.…”
Section: Introductionmentioning
confidence: 99%